Biodegradation of sodium dodecyl sulphate using locally isolated Pseudomonas aerugínosa sp. strain D1 - Mahamood, Mazurin (2012)
Surfactants are synthetic organic chemicals that are formulated to have cleansing or solubilisation properties. With the development of the industrial economy and increase in population density, surfactants have become one of the most widely disseminated toxic substances to enter the aquatic environment, creating a serious environmental problem. High concentration of SDS in the environment may give negative influences to the folding of a polypeptide chain and changes the surface charge of the molecule in the organisms and thus will disrupt the ecosystem. Their toxicities to organisms have been demonstrated previously by many reserchers (Ying, 2006; Singh et al., 2002; Lewis, 1991; Utsunomiya et al., 1997; Mori et al., 2002). Therefore, biodegradation of SDS is important in order to ensure low concentration of SDS in the environment. Local microorganisms were used in this study as it has high ability to adapt with the local environment such as temperature, humidity and so on. The main objective of this study was to isolate, characterize and finally immobilize a local bacterium with the potential to degrade Sodium Dodecyl Sulphate (SDS), a widely used anionic surfactant. Samples for this study were collected from detergent-contaminated area from several locations in Malaysia including from car wash and laundry’s outlets, drains, sludge and soil samples as mentioned in methodology (section 3.2). Screening was carried out by the conventional enrichment culture technique and the bacterium was tentatively identified as Pseudomonas aeruginosa sp. strain D1 HM852751 using BiologTM GN plates and partial 16S rRNA phylogeny. The optimal growth conditions in minimal medium and for degradation of SDS by Pseudomonas aeruginosa sp. strain D1 HM852751 were at 30°C and at pH 6.5 using phosphate buffer system. Sodium nitrate; at 8 gL-1 was found to be the best nitrogen source. The isolated strain exhibited optimum growth at SDS concentration of 1 gL-1 but can tolerate up to 14 gL-1 SDS, indicating that this isolate was able to survive in a relatively high concentration of SDS. 100% of 1 gL-1 SDS was completely degraded after 5 and 2 days of incubation before and after optimization, respectively. Encapsulation or immobilization of microorganisms of interest is a new technique and has proven to be more efficient in biodegradation of pollutants. Hence the Pseudomonas aeruginosa sp. strain D1 HM852751 was immobilized using gellan gum to enhance the degradation of SDS by the selected isolate. Optimizations of different immobilization parameters were carried out. The optimum gellan gum concentration for immobilized Pseudomonas aeruginosa sp. to degrade SDS ranged from 0.8% to 0.85%. The optimum cell density was between 40 gL-1 to 50 gL-1and the optimum bead size was 4.5 mm with the initial cell loading of 250 beads. 1 gL-1 of SDS was successfully degraded within 8 hours by immobilized cells compared to 20 hours by the freely suspended cells which was a substantial reduction in the degradation time. The immobilized cells can be used up to 20 cycles with approximately 100% reduction of SDS. These findings indicates Pseudomonas aeruginosa sp. strain D1 have high ability to degrade SDS when it was immobilized in gellan gum and has high potential for future research.